associativity, entrepreneurship, indigenous communities, Colombian post-conflict. - Pitre-Redondo, Remedios; Cardona-Arbeláez, Diego; Hernández-Palma, Hugo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
In this paper, it is reported a research that seeks to know the features of the Colombian indian  with reference to his entrepreneurship, which is relevant to the challenges arising at the end of the armed conflict in Colombia. To collect the information required for an exploratory / descriptive approach analysis, a questionnaire to indigenous leaders linked to these communities in socio-economic cut programs was applied. The results show that the indigenous entrepreneur has a predilection for the traditional activities of his ethnicity: ecotourism, handicrafts and agriculture. Likewise, a clear orientation could be established to carry out to these activities in their places of origin and to establish associations according to common interests. It is concluded that entrepreneurship can play a fundamental role in the post-conflict period, taking into account that many displaced indigenous populations will return to their places of origin once peace is signed. In addition, it was possible to identify that the activities of ecotourism, such as agriculture, clothing and handicrafts are the most popular among indigenous people.